Calculation of Internal Force and Deformation of Overlying Soil Corrugated Arch Bridge Based on Plate and Shell Theory. (November 2019) - Zhao, Ruipeng
Abstract: The shell is the general name for the flat plate and the shell. The mechanics of the plate and shell are similar to those of the elastic mechanics. The differential plate element is taken at any point in the plate or shell. From the perspectives of statics, geometry and physics, the equilibrium differential equations and geometric equations corresponding to the plate or shell are derived. And physical equations, these equations reflect the relationship and constraints between internal and external forces, strain and displacement, strain and stress. Under certain boundary conditions, the unknowns are determined by the above related basic equations.